Chloride salt enhances plant resistance to biotic stresses - Yang, Yu-Bing; Yang, Chang; Zheng, Jia-Rui; Xu, Liang-Zheng; Yao, Nan (Frontiers in Plant Science, 2024)
Biotic stresses caused by bacterial and fungal pathogens damage crops; identifying treatments that enhance disease resistance provides important information for understanding plant defenses and sustainable agriculture. Salt stress affects crop yields worldwide; however, studies have focused on the toxic sodium ion, leaving the effects of the chloride ion unclear. In this study, we found that irrigation with a combination of chloride salts (MgCl2, CaCl2, and KCl) suppressed the cell death phenotype of the ceramide kinase mutant acd5. Chloride salt pre-irrigation also significantly limited the cell death caused by Pseudomonas syringae pv maculicola infection and inhibited the multiplication of this bacterial pathogen in a mechanism partially dependent on the salicylic acid pathway. Moreover, chloride salt pre-irrigation improved plant defenses against the fungal pathogen challenge, confining the lesion area caused by Botrytis cinerea infection. Furthermore, the growth of herbivorous larvae of Spodoptera exigua was retarded by feeding on chloride salt irrigated plants. Thus, our data suggest that treatment with Cl- increases broad spectrum resistance to biotic challenges.